Mosambik – „Afrikanischer Teufelskreislauf“ oder lineare Entwicklung? - David Hasenauer (Historia.scribere)
Mozambique - ";African vicious circle"; or linear development? This paper deals with Mozambique’s development since its independence in 1975. The question is, whether Mozambique got into the “African vicious circle” (Spielbüchler) or emerged  as so called quasi-government. As will be shown, there are some similarities to so called “failed states” on the one hand, but also some singularities only applying for Mozambique, pointing out that the state took a different construction than other African states.